(untitled) (Iter, 2022)
The article will focus on Aristotle’s classic definition of Aristocracy, analyzing the specific example of the city of Carthage and its aristocratic constitution, which was mentioned by Aristotle himself. The singularity of the political constitution of this North African city will be emphasized, becauseas it is an unknown case with certain special characteristics -whether positive or negative- for the study of antiquity, especially since Carthage did not belong to the Greek cultural context. Nevertheless, this city and its constitution followed a similar course in political evolution comparable to that of other Greek polis.